Bomb Harvest - Mordaunt, Kim
Verzio FF submission Laos: the most bombed country, per capita, on the planet. Australian bomb disposal specialist Laith Stevens has to train a new young “big bomb” team to deal with bombs left from the US “Secret War”, but meanwhile, the local children are out hunting for bomb scrap metal. This timely story vividly depicts the consequences of war and the incredible bravery of those trying to clear up the mess.